Features of the study contamination of sediments by the trace elements - Gleb Yu. Tolkachev; Boris I. Korzhenevskiy; Nikolay V. Kolomiytsev (RUDN Journal of Ecology and Life Safety)
Currently, the condition and quality of water in water objects under the influence of technogenic factors changes for the worse. Studies of sediments of reservoirs make it possible to identify unfavorable areas and identify sources of pollution. From the point of view of technogenic load, the most dangerous pollutants are microelements Cd, Zn, Pb, Cu, Cr, Co, Ni, As. This article presents the results of studies of the contamination of sediments of reservoirs with the listed microelements, assessed by igeo-classes - by the contamination of the sorbing fraction (less than 0.02 mm). Describes or provides references to methods used in conducting nature and laboratory studies, as well as calculations of pollution levels. To systematize the research, objects of various hierarchical levels were identified on the basis of long-term experimental work within the Volga basin. For taxa of different hierarchies, various areal and time survey modes are proposed. The picture of contamination of sediments of the studied reservoirs is presented, and trends in its changes in space and time are noted.